Ubiquitin-Proteasome Dependent Regulation of the GOLDEN2-LIKE 1 Transcription Factor in Response to Plastid Signals. Issue 1 (7th November 2016) - Tokumaru, Mitsuaki; Adachi, Fumi; Toda, Makoto; Ito-Inaba, Yasuko; Yazu, Fumiko; Hirosawa, Yoshihiro; Sakakibara, Yoichi; Suiko, Masahito; Kakizaki, Tomohiro; Inaba, Takehito
Abstract : Accumulation of the transcription factor GOLDEN2 - LIKE 1 in response to plastid signals is regulated by the ubiquitin - proteasome system in Arabidopsis thaliana. Abstract: Arabidopsis ( Arabidopsis thaliana ) GOLDEN2-LIKE (GLK) transcription factors promote chloroplast biogenesis by regulating the expression of photosynthesis-related genes. Arabidopsis GLK1 is also known to participate in retrograde signaling from chloroplasts to the nucleus. To elucidate the mechanism by which GLK1 is regulated in response to plastid signals, we biochemically characterized Arabidopsis GLK1 protein. Expression analysis of GLK1 protein indicated that GLK1 accumulates in aerial tissues. Both tissue-specific and Suc-dependent accumulation of GLK1 were regulated primarily at the transcriptional level. In contrast, norflurazon- or lincomycin-treated gun1 - 101 mutant expressing normal levels of GLK1 mRNA failed to accumulate GLK1 protein, suggesting that plastid signals directly regulate the accumulation of GLK1 protein in a GUN1-independent manner. Treatment of the glk1glk2 mutant expressing functional GFP-GLK1 with a proteasome inhibitor, MG-132, induced the accumulation of polyubiquitinated GFP-GLK1. Furthermore, the level of endogenous GLK1 in plants with damaged plastids was partially restored when those plants were treated with MG-132. Collectively, these data indicate that the ubiquitin-proteasome system participates in the degradation of Arabidopsis GLK1 in response to plastid signals.